Elevated Serum Levels of Interleukin-15 in Pemphigus Vulgaris Patients: A Potential Therapeutic Target - Kheirodin, Maedeh; Tehranchinia, Zohreh; Ketabi, Yasaman; Tavakolpour, Soheil; Dadkhahfar, Sahar; Faghankhani, Masoomeh; Vahidnezhad, Hassan; Mozafari, Nikoo (Dermatology Practical & Conceptual, 2022)
introduction: IL-15 as a member of the immunoregulatory cytokines family is associated with the development of the autoimmune or chronic inflammatory disease. objectives: The goal of this study was to evaluate the serum levels of IL-15 in patients with pemphigusvulgaris and assess the association of IL-15 with anti-desmoglein antibodies and the severity ofthe disease.methods: fifty-three individuals affected with active pemphigus Vulgaris and 38 age and gender-matched healthy controls were enrolled in this study. Clinical characteristics and Autoimmune Bullous Skin Disorder Intensity Score (ABSIS) were assessed. Serum levels of IL-15 (pg/mL) and anti-desmoglein antibodies (Dsg1, 3) were measured.Result: The serum level of IL-15 in the patient group was assumed to be statistically higher thanthat of the control group (3.71 ± 1.5 vs. 0.79 ± 1.03 (p< 0.001)). A positive correlation was foundbetween serum levels of IL-15 and severity of pemphigus Vulgaris measured by ABSIS (r=0.5,p=0.04). No significant relationship was detected between the serum level of IL-15 and antidesmoglein antibodies (Dsg1 or Dsg3). (p=0.6 and p=0.9, respectively).Conclusion: our findings showed that levels of IL‐15 were elevated in the sera of pemphiguspatients and were related to disease severity. An increase in serum level of Il-15 in patients withpemphigus Vulgaris and its relation with disease severity suggest that this cytokine may play arole in the pathogenesis of the disease and targeting IL-15 will likely provide a newperspective on the treatment of this disease.